4(x-3)+6=2(x+1)

Simple and best practice solution for 4(x-3)+6=2(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+6=2(x+1) equation:


Simplifying
4(x + -3) + 6 = 2(x + 1)

Reorder the terms:
4(-3 + x) + 6 = 2(x + 1)
(-3 * 4 + x * 4) + 6 = 2(x + 1)
(-12 + 4x) + 6 = 2(x + 1)

Reorder the terms:
-12 + 6 + 4x = 2(x + 1)

Combine like terms: -12 + 6 = -6
-6 + 4x = 2(x + 1)

Reorder the terms:
-6 + 4x = 2(1 + x)
-6 + 4x = (1 * 2 + x * 2)
-6 + 4x = (2 + 2x)

Solving
-6 + 4x = 2 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-6 + 4x + -2x = 2 + 2x + -2x

Combine like terms: 4x + -2x = 2x
-6 + 2x = 2 + 2x + -2x

Combine like terms: 2x + -2x = 0
-6 + 2x = 2 + 0
-6 + 2x = 2

Add '6' to each side of the equation.
-6 + 6 + 2x = 2 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 2 + 6
2x = 2 + 6

Combine like terms: 2 + 6 = 8
2x = 8

Divide each side by '2'.
x = 4

Simplifying
x = 4

See similar equations:

| 2x-2=10x+1 | | 8+2x=5x-13 | | n+18=7 | | 10x-x-2x-x= | | 11x+25=7x+5 | | -3x-9=2x+7 | | -7r-3+2r= | | 3(2x+2)-4=5(x+1) | | .06+0.08(100-x)=4.2 | | 11x+13y=90 | | x^2-112=20x | | -8x-4x= | | -2(2x-4)=3(-12x+24) | | 2(6x+9)= | | 8x+20+16x-8=180 | | x^2+112=20 | | 4(-2)*2=8(-2)+3(-2)+6 | | 8+15i=2ni+3ni | | -12r=52+(-4) | | x-13=-34 | | 2x+5-6(x+1)=7x-5 | | 32x+6=12x-4 | | x-3*x=40 | | 2(x+1)=6+3x | | 8x-x=-49 | | -24x+x= | | 5(-4+2y)-3y=1 | | (-16)=(-19)-w | | 14q=-21 | | 2-5a-b=4 | | (x+12)*8=4*x | | -5c=-35 |

Equations solver categories